Problematyka pochówków oraz kultu zmarłych w orzecznictwie Europejskiego Trybunału Praw Człowieka - Jakuszewicz, Adam (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
In the jurisprudence of the European Court of Human Rights the rights connected with respect for the dead, especially the right to attend the funeral of a close relative by prisoners, are perceived as an integral part of the right to respect for private and family life. When undertaking any action related to the death of a person, public authorities should proceed with special diligence and prudence
Keywords: respect for private and family life; respect for the dead; right to participate in the funeral of a close family member; legal protection of the resting places of the dead